Iron‐ and Cobalt‐Catalyzed Synthesis of Carbene Phosphinidenes. Issue 5 (8th December 2015) - Pal, Kuntal; Hemming, Oliver B.; Day, Benjamin M.; Pugh, Thomas; Evans, David J.; Layfield, Richard A.
Abstract: In the presence of stoichiometric or catalytic amounts of [MN(SiMe3 )2 2 ] (M=Fe, Co), N‐heterocyclic carbenes (NHCs) react with primary phosphines to give a series of carbene phosphinidenes of the type (NHC)⋅PAr. The formation of (IMe4 )⋅PMes (Mes=mesityl) is also catalyzed by the phosphinidene‐bridged complex [(IMe4 )2 Fe(μ‐PMes)]2, which provides evidence for metal‐catalyzed phosphinidene transfer. Abstract : Carbene phosphinidenes of the type (NHC)⋅PAr (NHC=N‐heterocyclic carbene) can be synthesized using a catalytic phosphinidene‐transfer reaction between primary phosphines and NHCs, with the simple iron or cobalt amide, [MN(SiMe3 )2 2 ] (M=Fe or Co), as the catalyst.